RUSSIAN RURAL SOCIOLOGY: ITS SOCIAL SPACE, SUBJECT SPECIFICITY AND GENESIS - V. Novikov (Publishing House of the State University of Management, 2018)
The concepts of rural sociology (very interesting, but not to the end methodologically and theoretically grounded eld of sociology), its disciplinary specicity, the main content and concepts, the place in the system of classical and post-classical sociology, genesis and the main modern research schools are considered. Rural sociology is understood as a complex of knowledge of rural space of social life, at the same time - it is a branched theoretical and applied direction, a certain section in the general system of sociological eld. The social space of rural sociology is dichotomous urban, the opposite and at the same time ontologically similar to it by virtue of genetic relations, the social sphere of the village.